Molecular Mechanisms in Legionella Pathogenesis - Hilbi, Hubert.; Hilbi, Hubert. (Current Topics in Microbiology and Immunology,, 2014)
Legionnaires’ disease, a potentially fatal type of pneumonia primarily affecting elderly and immuno-compromised persons, is caused by the ubiquitous environmental bacterium Legionella pneumophila. This book offers authoritative reviews of different facets of its virulence, focusing on comparative phagocyte infection, virulence gene regulation, biochemical functions of effector proteins and cellular pathogen-host interactions, as well as host responses and immunity to L. pneumophila. Taken together, the contributions in this compilation provide a state-of-the-art overview of current insights into the molecular pathogenesis of the opportunistic and potentially fatal pathogen L. pneumophila.